Granting of License Polygamy PerspectiveMaqasid: Analysis of Article 4 of Law Number 1 of 1974 and Article 57 of the Compilation of Islamic Law - Ahmad Rezy Meidina (Indonesian Academy of Social and Religious Research (IASRR), 2022)
This article I focus on the reasons for granting polygamy permission for a man as contained in the provisions of Article 4 of Law No. 1 of 1974 and Article 57 Compilation of Islamic Law using the approach of ushul fiqh. Polygamy is an issue in Islamic family law both in classical jurisprudence and in contemporary jurisprudence. Islamic marriage law allows husbands to commit polygamy with a maximum of four as in the QS. An-Nisa verse (3) among scholars have different opinions about the provisions of polygamy, there are those who allow it with loose requirements and there are also some scholars who require it strictly. The granting of polygamy permission is very relevant to the concept of sharia maqasid in the aspect of daruriyat, which is to protect the offspring (children) in article 4 of Law No. 1 of 1974 and article 57 KHI if a wife is unable to give birth or give offspring then the husband has the right to propose to marry more than one wife.